Hyperglycemia in stroke and possible treatments. (1st June 2013) - Li, William A; Moore-Langston, Shannon; Chakraborty, Tia; Rafols, Jose A; Conti, Alana C; Ding, Yuchuan
Abstract : Hyperglycemia affects approximately one-third of acute ischemic stroke patients and is associated with poor clinical outcomes. In experimental and clinical stroke studies, hyperglycemia has been shown to be detrimental to the penumbral tissue for several reasons. First, hyperglycemia exacerbates both calcium imbalance and the accumulation of reactive oxygen species (ROS) in neurons, leading to increased apoptosis. Second, hyperglycemia fuels anaerobic energy production, causing lactic acidosis, which further stresses neurons in the penumbral regions. Third, hyperglycemia decreases blood perfusion after ischemic stroke by lowering the availability of nitric oxide (NO), which is a crucial mediator of vasodilation. Lastly, hyperglycemia intensifies the inflammatory response after stroke, causing edema, and hemorrhage through disruption of the blood brain barrier and degradation of white matter, which leads to a worsening of functional outcomes. Many neuroprotective treatments addressing hyperglycemia in stroke have been implemented in the past decade. Early clinical use of insulin provided mixed results due to insufficiently controlled glucose levels and heterogeneity of patient population. Recently, however, the latest Stroke Hyperglycemia Insulin Network Effort trial has addressed the shortcomings of insulin therapy. While glucagon-like protein-1 administration, hyperbaric oxygen preconditioning, and ethanol therapy appear promising, these treatments remain in their infancy and more research is needed to better understand the mechanisms underlying hyperglycemia-induced injuries. Elucidation of these mechanistic pathways could lead to the development of rational treatments that reduce hyperglycemia-associated injuries and improve functional outcomes for ischemic stroke patients.